Analisis Pendukung dan Penghambat Transformasi Digital dalam Perilaku Organisasi Kesatuan Mahasiswa Hindu Dharma Indonesia Tingkat Pusat dan Cabang Bogor - Ni Putu Aprilita Widiantari; Untung Suhardi; Indra Prameswara; I Made Jaya Negara Suarsa Putra; I Made Biasa (Samsara Institute Publisher, 2026)
Digital transformation in Hindu student organizations presents new challenges and opportunities, particularly in the context of organizational behavior. This study examines how the Indonesian Hindu Dharma Student Union (KMHDI), both at the Central Leadership (PP) and Bogor Branch Leadership (PC) levels, navigate these dynamics. The research focuses on the supporting and inhibiting factors of digital transformation that influence organizational communication and behavior. This study employed a qualitative method with a case study approach. Data were obtained through in-depth interviews with nine informants, including central and branch administrators, community leaders, and academics. Findings indicate that digital infrastructure support, the commitment of young, tech-savvy administrators, and the flexibility of digital platforms such as Zoom and WhatsApp are contributing factors to the transformation. However, limited digital literacy, resistance to change, lack of access to official central media, and minimal external support are key challenges. The information gap between the central and branch levels also impacts the spirit of cadre development and a sense of belonging to the organization. While digital transformation can increase efficiency, it also changes communication patterns and closeness among members. For organizational sustainability, KMHDI needs to align technology with a culture of camaraderie, strengthen digital literacy, and develop an inclusive, hybrid communication strategy. This research contributes to the development of a communication strategy for Hindu student organizations in navigating the digital era in an adaptive and sustainable manner.